# Calculator search results

Formula
$$x ^ { 2 } - 6 x + 9 = 0$$
$x = 3$
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 6 \right ) \pm \sqrt{ \left ( - 6 \right ) ^ { 2 } - 4 \times 1 \times 9 } } { 2 \times 1 }$
 Simplify Minus 
$x = \dfrac { 6 \pm \sqrt{ \left ( - 6 \right ) ^ { 2 } - 4 \times 1 \times 9 } } { 2 \times 1 }$
$x = \dfrac { 6 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 6 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times 9 } } { 2 \times 1 }$
 Remove negative signs because negative numbers raised to even powers are positive 
$x = \dfrac { 6 \pm \sqrt{ 6 ^ { 2 } - 4 \times 1 \times 9 } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 6 \pm \sqrt{ 6 ^ { 2 } - 4 \times 1 \times 9 } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 6 \pm \sqrt{ 0 } } { 2 \times 1 } }$
$x = \dfrac { 6 \pm \sqrt{ \color{#FF6800}{ 0 } } } { 2 \times 1 }$
$n square root$ of 0 is 0 
$x = \dfrac { 6 \pm \color{#FF6800}{ 0 } } { 2 \times 1 }$
$x = \dfrac { 6 \pm 0 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 6 \pm 0 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 6 \pm 0 } { 2 } }$
 The value will not be changed even if adding or subtracting 0 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 6 } { 2 } }$
$x = \color{#FF6800}{ \dfrac { 6 } { 2 } }$
 Do the reduction of the fraction format 
$x = \color{#FF6800}{ \dfrac { 3 } { 1 } }$
$x = \color{#FF6800}{ \dfrac { 3 } { 1 } }$
 Reduce the fraction to the lowest term 
$x = \color{#FF6800}{ 3 }$
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture